Gas Partial Pressure in Cultured Cells: Patho-Physiological Importance and Methodological Approaches - Farré, Ramon; Almendros, Isaac; Montserrat, Josep M.; Gozal, David; Navajas, Daniel (Frontiers in Physiology, 2018)
Gas partial pressures within the cell microenvironment are one of the key modulators of cell pathophysiology: respiratory gases (O2 and CO2) are usually altered in respiratory disease owing to reduced alveolar ventilation and/or decreased lung diffusion, and gasotransmitters (i.e., CO, NO, H2S) have been proposed as potential therapeutic agents. Investigating the pathophysiology of respiratory diseases in vitro mandates that cultured cells are subjected to gas partial pressures similar to those experienced by each cell type in its native microenvironment. For instance, O2 partial pressures range from ~13% in the arterial endothelium to values as low as 2-5% in cells of other healthy tissues and to less than 1% in solid tumor cells, clearly much lower values than those used in conventional cell culture research settings (~19%). Moreover, actual cell O2 partial pressure in vivo changes with time, at considerably different timescales as illustrated by tumors, sleep apnea, or mechanical ventilation. Unfortunately, the conventional approach to modify gas concentrations at the above culture medium precludes tight and exact control of intra-cellular gas levels to realistically mimic the natural cell microenvironment. Interestingly, well-controlled cellular application of gas partial pressures is currently possible through commercially available silicone-like material (PDMS) membranes which are biocompatible and have high permeability to gases. Cells are seeded on one side of the membrane and tailored gas concentrations are circulated on the other side of the membrane. Using thin membranes (50-100 µm) the value of gas concentration is instantaneously (< 0.5 s) transmitted to the cell microenvironment. As PDMS is transparent, cells can be concurrently observed by conventional or advanced microscopy. This procedure can be implemented in specific-purpose microfluidic devices and also in settings that do not require expensive or complex technologies, and that are thus readily implementable in any cell biology laboratory. This review describes the gas composition requirements for cell culture in respiratory research, the limitations of current experimental settings, and also suggests new approaches for better controlling gas partial pressures in cell culture.